Platinum Metal Complexes of Carbaboranylphophines: Potential Anti Cancer Agents - Maulana, Ilham; Loennecke, Peter; Hey-Hawkins, Evamarie (Indonesian Research Gateway, 2010)
PolyhedralÃÂ heteroboranes in particular dicarba-closo-dodecaboranes(12) and their organic derivatives have been the subject of intense research for over 40 years due to their unique chemical and physical properties. The initial attraction to dicarba-closo-dodecaboranes(12) In the medicinal chemistry research, was a result of their high boron content and stability to catabolism, which are important criteria for cancer therapy, such as BNCT (boron neutron capture therapy) agents. The coordination compounds of the platinum group metals have also received large interest for their potential application as chemotherapeutic agents, sinceÃÂ cis-diamminedichloroplatinum(II), cisplatin, has been reported to haveÃÂ capability as tumor inhibitor. Hence, applications can be envisioned for relatedÃÂ cis platinum complexes. Complex ofÃÂ cis-rac-[PtCl21,2-(PRCl)2C2B10H10] (R=Ph,ÃÂ tBu, NEt2, NPh2) have been synthesized by employing known carbaborane based phosphine ligands of clorophoshino-closo-dodecaborane , with complex ofÃÂ cis-[PtCl2(COD)] (COD = 1,5-cyclooctadiene) in an N2-atmosphere. The obtained complexes possess expected structure configuration, namelyÃÂ cis-rac.ÃÂ The characterization of the complex has been carried out using 1H,ÃÂ 31P,ÃÂ 13C andÃÂ 11B-NMR (Nuclear Magnetic Resonance), X-ray of single crystals, elemental analysis, IR (infra red) and mass spectroscopy (MS). TheÃÂ 31P1H NMR spectra of all the platinum complexes distinctly show the typical platinum satellites which are attributed to 31P-195Pt-coupling, in which the 31P1H NMR spectrum exhibits three lines with an intensity ratio of ca. 1:4:1. The structure of the platinum complexes consists of a slightly distorted square-planar coordination sphere, in which the platinumÃÂ atom is bonded to two chlorides and two phosphorus atoms of the chelating carbaboranylphosphine. Thus the platinum atoms exhibit the coordination number four, which is preferred in platinum(II) complexes.